Analysis of elite swimmers' activity during an instrumented protocol - David, A.; Poizat, G.; Gal-Petitfaux, N.; Toussaint, H.; Seifert, M. L. (Journal of Sports Sciences, 2009)
The aim of this study was to examine swimmers' activity-technical device coupling during an experimental protocol (MAD-system). The study was conducted within a course-of-action theoretical and methodological framework. Two types of data were collected: (a) video recordings and (b) verbalizations during post-protocol interviews. The data were processed in two steps: (a) reconstruction of each swimmer's course of action and (b) comparison of the courses of action. Analysis from the actors' point of view allowed a description of swimmer-technical device coupling. The results showed that the technical device modified the athletes' range of perceptions and repertoire of actions. They also indicated that changes in coupling between the swimmers and the MAD-system were linked to utilization constraints: the swimmers' experiences were transformed in the same speed intervals, suggesting that this was an essential situational constraint to swimmer-technical device coupling. This study highlights how a technical device and the conditions of its use changed athletes' activity and suggests that it is important to develop activity-centred design in sport.